Crystallization in Sb0.5Se99.5 glass studied under and without protective atmosphere - Honcová, Pavla; Pilný, Petr; Stehlík, Stanislav; Košťál, Petr (University of Pardubice, 2017)
The crystallization in a Sb0.5Se99.5 glass was studied by DSC method. The manipulation with amorphous samples was done under the protective atmosphere of argon and also without this protection, by simply exposing to the air. The obtained DSC traces as well as their kinetic characterization have shown that the atmosphere during the manipulation with amorphous material has significant influence on its crystallization behaviour.